(untitled) (Journal of Cancer Research Updates, 2015)
We present herein a case of a 24-year-old woman with incidentally diagnosed right adrenal ganglioneuroma with 14cm in size that was removed completely by the laparoscopic approach. The patient was asymptomatic and the tumor was first diagnosed on abdominal ultrasonography. A subsequent computed tomography (CT) of the abdomen confirmed a 12x 11x9cm complex expansive mass of right adrenal, with well-defined outlines. Magnetic resonance imaging (MRI) showed a solid lesion measuring 11 x 9 x 11cm arising from the right adrenal. Laparoscopic complete excision of the mass was accomplished through a transabdominal lateral approach. The surgical specimen weighed 665 g and 14 x 10 x 7 cm in size. There was no complication in postoperative period, and the patient was released from the hospital two days after the operation. The patient resumed her normal activities in one week. Histology was consistent with an adrenal ganglioneuroma. A control CT was made one year after the surgery with no evidence of lesion suggestive of relapse. Adrenal ganglioneuromas are rare lesions with a benign behavior in which surgery is the only possible form of treatment. In centers of advanced laparoscopy this method of access can be used, even for larger lesions.